EXPLOSION SEISMIC REFLECTIONS FROM THE EARTH'S CORE - Thybo H.; Ross A.R.; Egorkin A.V. (My University, 2003)
Recent seismological studies have presented evidence for the existence of a layer with ultra-low seismic velocities at the core–mantle boundary at ca. 2900 km depth. We report high-amplitude, high-frequency, and laterally coherent seismic arrivals from three nuclear explosions in Siberia. With recording station intervals of 15 km, the seismic phases are readily correlated and show the presence of a thin, ultra-low velocity zone in a region where it was not previously reported. The duration and complexity of the arrivals are inconsistent with a simple core–mantle boundary and require a hitherto unidentified, kilometre-scale, fine structure in the ultra-low velocity zone. The observations may be explained by a ca. 7 km thick, two-layer, ultra-low velocity zone with exceptional low velocities, which indicate the presence of high percentages of melt (>15%), in particular in the lower part of the zone. Waveform variation implies lateral change in the thickness and physical properties of the ultra-low velocity zone with a wavelength of less than 100 km.